Being Good by Doing Good: Goodness and the Evaluation of Persons. Issue 1 (17th June 2016) - SCHMIDT, ANDREAS T.
Abstract : Does doing good in itself make one a better person? This idea is intuitive yet its precise formulation underexplored. This article first shows that it is not the case that a person is good to the extent that her existence brings about good or to the extent that her actions do good. A proportional principle that evaluates a person according to the expected goodness of her actual course of action relative to the expected goodness of other available courses is shown to be the most plausible candidate. However, such a principle can only be a pro tanto principle of what makes persons good. To account for other relevant intuitions – such as that a person's motives matter for how good she is – we need further principles. This article ends with a few practical implications about how to be a better person according to the principle defended here.